2014
DOI: 10.14569/ijacsa.2014.051206
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Analyis of Public ICT Development Project Objectives in Hungary

Abstract: Abstract-E-government development in most European

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…As I referred to this in the introduction, Hungarian government is going to spend 400 million Euros on more than 30 major IT projects modernizing administration. In an earlier study we have shown that in the period of 2007 -2013, when a similar undertaking took place, result were quite ambiguous, both in deliverables and in absorption of financial resources [1]. Generally, this particular Hungarian problem appears in many other environments, which justifies the need for a thorough investigation in the area of public information project management.…”
Section: Success and Failour Factors Of Public Information System Project Managementmentioning
confidence: 98%
See 1 more Smart Citation
“…As I referred to this in the introduction, Hungarian government is going to spend 400 million Euros on more than 30 major IT projects modernizing administration. In an earlier study we have shown that in the period of 2007 -2013, when a similar undertaking took place, result were quite ambiguous, both in deliverables and in absorption of financial resources [1]. Generally, this particular Hungarian problem appears in many other environments, which justifies the need for a thorough investigation in the area of public information project management.…”
Section: Success and Failour Factors Of Public Information System Project Managementmentioning
confidence: 98%
“…Hungary´s public administration reform is entirely founded from European Social Cohesion and Structural Funds [1], [2]. The Commission has approved the key objectives and deliverables for the absorption of 795mEuro focusing on two key areas: a) reduction of administrative burden and b) enforcing service orientation and ethical operation in public services.…”
Section: Digital Governance Research Program: Strategic Environment and Objectivesmentioning
confidence: 99%
“…As a consequence of the outbreak of the global Covid-19 pandemic (stated by the WHO on 11 March 2020), severe lockdowns and restrictions were imposed by governments all over the world at high economic and societal costs. 1 In this environment, greater attention is being given to digital solutions and services. Digital solutions can mitigate the harmful economic effects of government interventions to control the pandemic and provide positive effects to public health interests.…”
Section: Introductionmentioning
confidence: 99%
“…The globalized and fast-paced business world together with a lot of other factors brings about a continuous increase in the volume of data [15]. Businesses have to discover the knowledge in the depths of overflowing data if they want to be successful.…”
Section: Introductionmentioning
confidence: 99%